Protocol for a mixed methods study of hospital readmissions: sensemaking in Veterans Health Administration healthcare system in the USA. Issue 4 (7th April 2018) - Penney, Lauren S; Leykum, Luci K; Noël, Polly; Finley, Erin P; Lanham, Holly Jordan; Pugh, Jacqueline
Abstract : Introduction: Effective delivery of healthcare in complex systems requires managing interdependencies between professions and organisational units. Reducing 30-day hospital readmissions may be one of the most complex tasks that a healthcare system can undertake. We propose that these less than optimal outcomes are related to difficulties managing the complex interdependencies among organisational units and to a lack of effective sensemaking among individuals and organisational units regarding how best to coordinate patient needs. Methods and analysis: This is a mixed method, multistepped study. We will conduct in-depth qualitative organisational case studies in 10 Veterans Health Administration facilities (6 with improving and 4 with worsening readmission rates), focusing on relationships, sensemaking and improvisation around care transition processes intended to reduce early readmissions. Data will be gathered through multiple methods (eg, chart reviews, surveys, interviews, observations) and analysed using analytic memos, qualitative coding and statistical analyses. We will construct an agent-based model based on those results to explore the influence of sensemaking and specific care transition processes on early readmissions. Ethics and dissemination: Ethical approval has been obtained through the Institutional Review Board of the University of Texas Health Science Center at San Antonio (approval number: 14–258 hour). We will disseminate our findings in manuscripts in peer-reviewed journals, professional conferences and through short reports back to participating entities and stakeholders.